Exploring Job Satisfaction: The Impact of Transformational Leadership and Interpersonal Communication on Work Discipline - Darusman Darusman; Arifuddin Arifuddin (International Journal of Management Science and Information Technology, 2025)
The research attempts to consider swept-away (transformational) leadership and interpersonal communication and their effect on job discipline of subordinates. Good work discipline is vital to improve production performance and organization effectiveness. Transformative leadership offers the possibility to enrich employment and provide motivation, leadership, organizational objectives. Good interpersonal communication helps create better connections between managers and subordinates. A survey research method was undertaken in calculating this data study, with 200 XYZ Company employees being respondents. The data was acquired on the basis of questionnaire scales used to gauge variables such as transformational leadership, interpersonal communication in their work group and work discipline. These tests all showed data that was both reliable and valid. The analysis of data used multiple linear regression. The findings have shown that efficacious leadership and good interspecialty communication bring a beneficial result. The experiment showed coefficients of 0.220 and 0.345, respectively. A manager who is able to both motivate and provide open lines of communication can raise staff discipline. This study proposes that organizations need to lay more emphasis on leadership quality and interaction within the workplace to increase employee discipline levels and effectiveness of work.